Family function and adolescent altruistic behavior: the multiple mediating effects of self-affirmation and psychological resilience - Cui, Hongbo; Bi, Xiaoyan; Zhou, Xiaowen; Zhang, Weixin; Ma, Yankun (Frontiers in Psychology, 2023)
The current study aimed to explore the relationship between family function and adolescent altruistic behavior, as well as the mediating effects of self-affirmation and psychological resilience in this relationship. A survey was conducted on 972 high school students in Guangdong Province using the Family APGAR, GHQ-Sense of Adequacy, Chinese version of Connor-Davidson Resilience Scale, and Altruistic Behavior Scale. Results found that the score of psychological resilience of males was significantly higher than that of females, but the score of altruistic behavior was significantly lower than that of females. Family function had a positive predictive effect on altruistic behavior. Psychological resilience played a mediating role between family function and altruistic behavior. Self-affirmation and psychological resilience played chain mediating roles between family function and altruistic behavior. This study indicated that family care is crucial for the development of adolescent altruistic behavior, and that it can promote the development of altruistic behavior through the enhancement of self-affirmation and psychological resilience.